APEC procurement principles influencing the legal framework of government procurement in Malaysia - Abdul Rahman, Rohana (2011)
This paper discusses the application of Asia Pacific Economic Cooperation (APEC) procurement principles in the legal framework of government procurement (government contracting) in Malaysia.Each principle governing government procurement under the APEC non-binding scheme is analysed to determine whether these APEC standards have been adopted by the Malaysian government in its national procurement procedures and processes.The paper finds that there is a strong linkage between these APEC standards and the current principles and policy on government procurement in Malaysia. However, there are challenges faced by Malaysia in applying the said standards. The paper suggests that APEC standards are useful to strengthen Malaysia s effort to reform its national procurement system.